Determinants of Corporate Value and Corporate Social Responsibility - Setyo Liyundira, Fetri; Wiyono, M. Wimbo (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This study was designed using the profitability variable as the independent variable, and firm value as the dependent variable, while corporate social responsibility as the moderating variable. Basically, the value of the company is one aspect that is quite important in the world of investment. Because company value can be interpreted as the price a prospective buyer is willing to pay if the company is sold (Husnan, 2000: 7). The significant effect of profitability on firm value is in line with the signal theory (signaly theory). Profitability is a signal in the form of information stating that the company is better than other companies. Profitability is also able to reduce information asymmetry, because profitability is reliable financial information and will reduce uncertainty about the company's future prospects. Corporate Social Responsibility (CSR) has a positive effect on the relationship between profitability and firm value in manufacturing companies in the period 2013-2015. This shows that the existence of CSR is still able to strengthen the relationship between the effect of profitability on firm value